A Prospective Randomized Controlled Trial of AJG522 versus Standard PEG + E as Bowel Preparation for Colonoscopy. (22nd January 2015) - Sagawa, Toshihiko; Sato, Ken; Tomizawa, Taku; Mizuide, Masafumi; Yasuoka, Hidetoshi; Shimoyama, Yasuyuki; Kuribayashi, Shiko; Kakizaki, Satoru; Kawamura, Osamu; Kusano, Motoyasu; Yamada, Masanobu
Abstract : Polyethylene glycol- (PEG-) based bowel preparations for colonoscopies are often poorly tolerated due to the large volumes of fluid intake required. We compared low-volume "modified" PEG + ascorbic acid (AJG522) with standard PEG with electrolytes (PEG + E) in addition to a stimulant laxative and an agent to improve bowel function for the bowel cleansing before colonoscopy to evaluate its efficacy, safety, and acceptability. Outpatients scheduled to undergo colonoscopy were randomized to receive either AJG522 or PEG + E. Bowel cleansing conditions were assessed via macroscopic fecal findings by blinded and independent investigators. A survey of the patients' feedback regarding the preparation was conducted by questionnaire. Successful cleansing was achieved in all cases, except for 4 cases in the PEG + E group, at 3 hours after taking the preparation. The fecal properties were significantly clearer in the AJG522 group than in the PEG + E group at 2 hours after taking each preparation P = 0.013 . Although the total liquid volume of the bowel preparation was not reduced, the AJG522 preparation could significantly reduce the required volume of the preparation P < 0.0001 . Moreover, the patients in the AJG522 group had better acceptability P = 0.010 . There were no significant differences in the safety profiles between groups (UMIN000013892 ).